Differential expression of microRNAs and potential targets under drought stress in barley. (4th August 2016) - Ferdous, Jannatul; Sanchez‐Ferrero, Juan Carlos; Langridge, Peter; Milne, Linda; Chowdhury, Jamil; Brien, Chris; Tricker, Penny J.
Abstract: Drought is a crucial environmental constraint limiting crop production in many parts of the world. microRNA (miRNA) based gene regulation has been shown to act in several pathways, including crop response to drought stress. Sequence based profiling and computational analysis have revealed hundreds of miRNAs and their potential targets in different plant species under various stress conditions, but few have been biologically verified. In this study, 11 candidate miRNAs were tested for their expression profiles in barley. Differences in accumulation of only four miRNAs ( Ath ‐miR169b, Osa ‐miR1432, Hv ‐miRx5 and Hv ‐miR166b/c) were observed between drought‐treated and well‐watered barley in four genotypes. miRNA targets were predicted using degradome analysis of two, different genotypes, and genotype‐specific target cleavage was observed. Inverse correlation of mature miRNA accumulation with miRNA target transcripts was also genotype dependent under drought treatment. Drought‐responsive miRNAs accumulated predominantly in mesophyll tissues. Our results demonstrate genotype‐specific miRNA regulation under drought stress and evidence for their role in mediating expression of target genes for abiotic stress response in barley. Abstract : A role for microRNAs in regulating gene responses to abiotic stress has been well established but translating this information to practical crop improvement has proved difficult, because we have had little knowledge about genotypic stress‐induced variation in expression of miRNAs and their targets. MicroRNA/gene target interaction is usually predicted from bioinformatic analysis of small RNA and degradome sequencing data. Of 11 predicted, drought‐regulated microRNAs we were able to show inverse correlation of only two microRNA/ target pairs under drought, and this was genotype dependent. Our results show genotypic variation in miRNA expression and provide evidence of drought‐responsive regulation of important microRNA target genes.